The education of Muslim women in Daesh's and Al Qaeda's online magazines. Issue 3 (4th May 2021) - Llorent-Bedmar, Vicente; Cobano-Delgado Palma, Verónica; Navarro-Granados, María
ABSTRACT: Violent radicalisation is one of the most serious problems jeopardising the peaceful coexistence of many modern societies. In recent years, different research has been performed on the processes of violent radicalisation linked to terrorism and instigated by men. Following the recent increase in the number of women joining Daesh or Al Qaeda, this study examines the persuasive messages that both convey to Muslim women through their official online magazines. Using Atlas.ti software, a qualitative content analysis was conducted on all the articles aimed specifically at women published in these magazines. These groups see women as the cornerstone of the Muslim community, assigning them a key role in its survival and highlighting their contribution to the reproduction and education of future generations. Nonetheless, it has been possible to detect differences and contradictions in the role that these groups give women in violent jihad. The results obtained here contradict the general assertion that women are prompted to join these groups by promises of romance, pointing instead to different factors making them more vulnerable to influence. In conclusion, real decolonisation and educational preventive measures on which a consensus has been reached with the Muslim community are recommended.